2020
DOI: 10.1097/corr.0000000000001576
|View full text |Cite
|
Sign up to set email alerts
|

Does a History of Slipped Capital Femoral Epiphysis in Patients Undergoing Femoroacetabular Osteoplasty for Femoroacetabular Impingement Affect Outcomes Scores or Risk of Reoperation?

Abstract: Background Femoroacetabular impingement (FAI) can occur after slipped capital femoral epiphysis (SCFE) regardless of slip severity and even after in situ pinning. These patients represent a rare and unique demographic that is largely unreported on. It is important to further characterize the clinical presentation of these patients, associated treatment modalities, and the efficacy of these treatment modalities. Questions/purposes (1) How do patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In the current study, Sutton and colleagues [8] performed a retrospective, propensity score–matched, controlled study comparing 2-year minimum results following femoroacetabular osteoplasty (FAO) via the anterior mini-open approach in patients with post-SCFE deformity to those with femoroacetabular impingement (FAI) without a history of SCFE. The anterior mini-open approach was previously promoted by Parvizi and his group [6] for use in FAI without an explicit history of SCFE, reporting both a relatively low frequency of conversion to THA (9.6%) and improvements in multiple patient-reported outcome scores 2 years after surgery.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, Sutton and colleagues [8] performed a retrospective, propensity score–matched, controlled study comparing 2-year minimum results following femoroacetabular osteoplasty (FAO) via the anterior mini-open approach in patients with post-SCFE deformity to those with femoroacetabular impingement (FAI) without a history of SCFE. The anterior mini-open approach was previously promoted by Parvizi and his group [6] for use in FAI without an explicit history of SCFE, reporting both a relatively low frequency of conversion to THA (9.6%) and improvements in multiple patient-reported outcome scores 2 years after surgery.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The authors of the current study found that while those with post-SCFE FAI presented with greater radiographic deformity and were more likely to have labral and chondral damage, the risk of conversion to THA was not different between patients with post-SCFE deformity and those with FAI who had no history of SCFE [8].…”
Section: Where Are We Now?mentioning
confidence: 99%
See 2 more Smart Citations